The Sustainability of Women’s SMEs During COVID-19 Pandemic - Genoveva, Genoveva (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2021)
The COVID-19 pandemic has momentously affected the world economy, including Indonesia, whose economy decreased by -2.07% in 2020. This phenomenon has presented monumental challenges and put heavy pressure on women entrepreneurs as social norms in Indonesia generally require women to bear the responsibility of taking care of household affairs. Meanwhile, a successful women-run business is typically characterized by personality, competence, and environmental support surrounding her. Therefore, in ensuring business sustainability, affording flexibility for women in running a business is needed. One way to achieve the goal is through running a business through digital means during economic downturns such as the COVID-19 pandemic. The research method used in this study is a quantitative method using an online questionnaire distributed to 250 women entrepreneurs as a data collection tool. Data were thereupon processed by using Amos, with the Structural Equation Model (SEM) application. This study shows that environmental competence and support have a consequential effect on organizational flexibility, while personality does not influence organizational flexibility. This study also finds that organizational flexibility significantly affects company performance.